Clinical effects of cardiac contractility modulation (CCM) as a treatment for chronic heart failure - Borggrefe, Martin; Burkhoff, Daniel (European journal of heart failure, 2012)
Cardiac contractility modulation (CCM) signals are non?excitatory signals applied during the absolute refractory period that have been shown to enhance the strength of left ventricular contraction without increasing myocardial oxygen consumption in studies carried out in animals and humans with heart failure and reduced ejection fraction. Studies from myocardial tissue of animals and humans with heart failure suggest that the mechanisms of these effects is that CCM drives expression of many genes that are abnormally expressed in heart failure towards normal, including proteins involved with calcium cycling and the myocardial contractile machinery. Clinical studies have primarily focused on patients with normal QRS durations in view of the fact that cardiac resynchronization (CRT) is a viable option for patients with prolonged QRS duration. These studies show that CCM improves exercise tolerance as indexed by peak oxygen consumption (VO2) and quality of life indexed by the Minnesota Living with Heart Failure Questionnaire. The device is currently available for clinical use in countries recognizing the CE mark and is undergoing additional testing in the USA under a protocol approved by the Federal Drug Administration.